You need to find out how many problems Carl can do in a minute (unit rate), which is 20/55 or .36363636363. If you multiply it by 75 mins, you get 27.27, so the answer would be 27.
Answer:
no it is 0.4
Step-by-step explanation:
5x(2-4)=2(5x-4)
10x-20x=10x-8
-20x=-8
20x=8
10x=4
x=0.4
Answer:
4.666666667 or 4.6_ (repeating decimal)
Answer:
![\displaystyle \frac{4q^2-q+3}{q^2+6q+5}-\frac{3q^2-q-6}{q^2+6q+5}=\frac{q^2+9}{q^2+6q+5}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B4q%5E2-q%2B3%7D%7Bq%5E2%2B6q%2B5%7D-%5Cfrac%7B3q%5E2-q-6%7D%7Bq%5E2%2B6q%2B5%7D%3D%5Cfrac%7Bq%5E2%2B9%7D%7Bq%5E2%2B6q%2B5%7D)
Step-by-step explanation:
<u>Simplifying Rational Expressions</u>
If two or more rational expressions have the same denominator, the add and subtract operations are done only with the numerator. The final denominator will be the common of both.
The expression is:
![\displaystyle \frac{4q^2-q+3}{q^2+6q+5}-\frac{3q^2-q-6}{q^2+6q+5}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B4q%5E2-q%2B3%7D%7Bq%5E2%2B6q%2B5%7D-%5Cfrac%7B3q%5E2-q-6%7D%7Bq%5E2%2B6q%2B5%7D)
Operating on the numerators:
![\displaystyle \frac{4q^2-q+3}{q^2+6q+5}-\frac{3q^2-q-6}{q^2+6q+5}=\frac{4q^2-q+3-(3q^2-q-6)}{q^2+6q+5}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B4q%5E2-q%2B3%7D%7Bq%5E2%2B6q%2B5%7D-%5Cfrac%7B3q%5E2-q-6%7D%7Bq%5E2%2B6q%2B5%7D%3D%5Cfrac%7B4q%5E2-q%2B3-%283q%5E2-q-6%29%7D%7Bq%5E2%2B6q%2B5%7D)
Removing parentheses:
![\displaystyle \frac{4q^2-q+3}{q^2+6q+5}-\frac{3q^2-q-6}{q^2+6q+5}=\frac{4q^2-q+3-3q^2+q+6}{q^2+6q+5}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7B4q%5E2-q%2B3%7D%7Bq%5E2%2B6q%2B5%7D-%5Cfrac%7B3q%5E2-q-6%7D%7Bq%5E2%2B6q%2B5%7D%3D%5Cfrac%7B4q%5E2-q%2B3-3q%5E2%2Bq%2B6%7D%7Bq%5E2%2B6q%2B5%7D)
Simplifying:
![\boxed{\displaystyle \frac{4q^2-q+3}{q^2+6q+5}-\frac{3q^2-q-6}{q^2+6q+5}=\frac{q^2+9}{q^2+6q+5}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cdisplaystyle%20%5Cfrac%7B4q%5E2-q%2B3%7D%7Bq%5E2%2B6q%2B5%7D-%5Cfrac%7B3q%5E2-q-6%7D%7Bq%5E2%2B6q%2B5%7D%3D%5Cfrac%7Bq%5E2%2B9%7D%7Bq%5E2%2B6q%2B5%7D%7D)
The expression cannot be further simplified.
Answer:
$599
Step-by-step explanation:
Given: Discount- 40% off on original price.
Gift card= $25
Total cost before taxes is $334.40
Lets assume the original price be "x".
We know there is 40% on original price and Perry uses $25 gift card.
Remember; Total cost= ![Original\ price- discount- gift\ card](https://tex.z-dn.net/?f=Original%5C%20price-%20discount-%20gift%5C%20card)
Now, finding the original price of Iphone.
⇒ ![x-0.40x-25= 334.40](https://tex.z-dn.net/?f=x-0.40x-25%3D%20334.40)
⇒ ![0.60x-25= 334.40](https://tex.z-dn.net/?f=0.60x-25%3D%20334.40)
Adding both side by 25
⇒![0.60x= 334.40+25](https://tex.z-dn.net/?f=0.60x%3D%20334.40%2B25)
⇒![0.60x= 359.4](https://tex.z-dn.net/?f=0.60x%3D%20359.4)
Dividing both side by 0.60
⇒ ![x= \frac{359.4}{0.60}](https://tex.z-dn.net/?f=x%3D%20%5Cfrac%7B359.4%7D%7B0.60%7D)
∴ ![x= 599](https://tex.z-dn.net/?f=x%3D%20599)
Hence, the original price of iphone is $599